Omega 3 fatty acid docosahexaenoic acid (DHA) mitigates inflammatory responses in experimental sepsis - Moraes, Bianca Portugal Tavares de; Moraes-de-Souza, Isabelle; de Souza Gomes-Reis, Gabrielle Lacerda; Ferreira-Costa, Marina; da Cunha, Carolina Medina Coeli; de Almeida, Matheus Augusto Patrício; Estato, Vanessa; Corrêa Souza e Souza, Kauê Francisco; dos Santos, Francisco da Silva; dos Santos Mascarenhas Brito, Maria Alice; Soares, Patrícia Novaes; Ferreira Peres, Wilza Arantes; et al. (Frontiers in Pharmacology, 2025)
BackgroundSepsis is a life-threatening condition characterized by organ dysfunction resulting from a dysregulated host response to infection. Sepsis induces systemic inflammation and increases adhesion molecule expression and activation, promoting leukocyte adhesion to the endothelium. In addition, sepsis leads to the disruption of vascular integrity with fluid leakage and migration of leukocytes across the compromised endothelial barrier, leading to organ damage. Bioactive food compounds such as DHA, an essential omega 3 polyunsaturated fatty acid (PUFA) in the Mediterranean Diet (MedDiet), are known for their anti-inflammatory and pro-resolving properties. Thus, the supplementation of DHA may affect sepsis development, protecting the host.MethodsTo investigate the role of DHA in neutrophil function, we conducted flow chamber assays using isolated neutrophils from mice and humans treated with DHA. To assess whether similar effects occur in vivo, we performed intravital microscopy of the TNF-stimulated cremaster muscle. Finally, we employed the cecal ligation and puncture (CLP) model to evaluate the therapeutic potential of DHA in experimental sepsis, and we applied intravital microscopy to assess cerebral vascular perfusion and the cerebral microcirculation in septic mice.ResultsWe found a significant reduction in neutrophil rolling and adhesion in DHA-treated neutrophils compared to controls in flow chamber assays, which can be mechanistically explained by a substantial reduction in adhesion markers, such as PSGL-1, CD11a, and CXCR4. Next, we employed intravital microscopy in the mouse cremaster muscle, stimulating it with tumor necrosis factor, and found a significant reduction in leukocyte rolling and adhesion in DHA-treated mice, confirming the in vitro flow chamber results. We also used a CLP model of sepsis. We found that DHA treatment ameliorated CLP-related sepsis parameters, including mortality, clinical score, total leukocyte and neutrophil transmigration, cytokine levels in peritoneal exudate, plasma, and brain tissue, and lactate levels. DHA treatment also improved cerebral microcirculatory perfusion and exhibited anti-inflammatory and pro-resolving effects, reflected by increased plasma and brain tissue resolving D1 and D2 levels.ConclusionTogether, we identify DHA as a promising anti-inflammatory therapeutic agent that mitigates sepsis-related vascular dysfunction and prevents organ failure.